State neutrality - János Kis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
There is a widespread agreement in modern democracies that a state should not force its citizens to lead lives they do not endorse themselves. It is also generally agreed that state acts should not be justified by appealing to the authority of religious books. Such claims are often reformulated as holding that state action should be neutral with respect to the ideals of the good life, or that the justification of state acts should be neutral with respect to basic beliefs. But does the use of the term neutral add anything important to the original wording? Does it point to a common principle - a principle of state neutrality (PSN) - that unites such judgments? If it does, what normative work PSN is supposed to do? What is its basis? What are the things towards which it requires the acts of the relevant type to be neutral? Such questions call for a theory of neutrality. The theory of neutrality has its natural home in the liberal tradition. Liberalism had a neutralist bent since its beginnings. But a systematic account of PSN was not laid out before the 1970s and '80s when John Rawls and others restated the foundations of liberal theory. While particular neutrality judgments are widely accepted, the general conception of liberal neutrality elicited strong critical reactions. Some of the critiques took liberalism's commitment to neutrality as evidence that the liberal view of the individual, society, and politics is deeply flawed. Others attacked liberal neutrality as reflecting a mistaken interpretation of what liberalism really is about. The debate subsided in the last decade or so, without settling, however, on a standard view. State neutrality remains a controversial idea. This article tries to spell out its main tenets and to explain how they hang together. It examines the central objections, and explores revisions that may enhance the theory's defensibility.
Keywords: 320; state action; principle of state neutrality; liberal neutrality; liberalism; theory of neutrality